2014
DOI: 10.15261/serdj.21.217
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Taxane Production by the Combination of <i>in situ</i> Extraction with Lauryl Alcohol and Elicitation by Methyl Jasmonate in a Suspension Callus Culture

Abstract: We report here on taxane production by a combination of in situ extraction with lauryl alcohol (LA) and elicitation by methyl jasmonate (MJ) in a suspension callus of Taxus cuspidata. LA is an effective organic solvent for the in situ extraction of paclitaxel which gives a decrease in the paclitaxel concentration in the medium thus reducing its feed-back inhibition against callus growth. Improved callus growth and increased production amounts of the taxanes were observed in the two phase systems including MJ, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Both these systems increased paclitaxel productivity [20][21][22][23][24]. Enhancements of callus growth and paclitaxel productivity in a lauryl alcohol (LA) medium two-phase culture system were achieved in previous studies [11,19,25,26]. In these culture systems, addition of MJ enhanced paclitaxel production but resulted in little callus growth [6].…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Both these systems increased paclitaxel productivity [20][21][22][23][24]. Enhancements of callus growth and paclitaxel productivity in a lauryl alcohol (LA) medium two-phase culture system were achieved in previous studies [11,19,25,26]. In these culture systems, addition of MJ enhanced paclitaxel production but resulted in little callus growth [6].…”
mentioning
confidence: 83%
“…For effective paclitaxel production, the cultures must be able to sustain growth while producing large amounts of paclitaxel simultaneously. To reduce inhibition caused by paclitaxel accumulation, two-phase culture systems using waterimmiscible organic solvents or solid absorbents have been used to recover paclitaxel from the culture medium in situ [17,[19][20][21][22][23][24][25][26][27]. Both these systems increased paclitaxel productivity [20][21][22][23][24].…”
mentioning
confidence: 99%
“…These phenomena were such because three elicitors generate different defense response signaling, but they are cross-linked in the signaling pathway and showed synergistic effects in increasing paclitaxel production. Other scholars have treated sequoia healing tissues, suspension cells, or hazelnut cells with CD + methyl jasmonate [57], SA + glucose [30], lauryl alcohol + methyl jasmonate [15], and ultrasound + SA [58], respectively; on this, they found that the paclitaxel yields were significantly higher than those obtained following single treatments. In particular, the paclitaxel yield of the Taxus Chinese suspension cells with SA and fungal elicitors was 1.5 times, 2.3 times, and 7.5 times higher than that of the fungal elicitor treatment group, SA treatment group, and the Control group, respectively [40].…”
Section: Paclitaxel Contentmentioning
confidence: 99%
“…Paclitaxel is a hydrophobic substance with cytotoxic properties [14]. Large accumulations in suspension cells inhibit cell growth and affect paclitaxel production [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation